Oxidative cleavage of allyl ethers by an oxoammonium salt. Issue 14 (6th March 2015) - Kelly, Christopher B.; Ovian, John M.; Cywar, Robin M.; Gosselin, Taylor R.; Wiles, Rebecca J.; Leadbeater, Nicholas E.
Abstract : A method to oxidatively cleave allyl ethers to their corresponding aldehydes mediated by an oxoammonium salt is described. Using a biphasic solvent system and mild heating, cleavage proceeds readily, furnishing a variety of α, β-unsaturated aldehydes and ketones. Abstract : A method to oxidatively cleave allyl ethers to their corresponding aldehydes mediated by an oxoammonium salt is described. Using a biphasic solvent system and mild heating, cleavage proceeds readily, furnishing a variety of α, β-unsaturated aldehydes and ketones.